A Unified Weight Formula for Calculating the Sample Variance from Weighted Successive Differences - Kuo-Hung Lo; Tien-Lung Sun; Juei-Chao Chen (Discrete Dynamics in Nature and Society)
The basic formula to calculate sample variance is based on the sum of squared differences from mean. From computational perspective, mean calculation is nondesired as it can introduce computing errors. Previous researches have proposed to use weighted formula of the successive differences to calculate sample variance to avoid mean calculation. But their weighted formula is not in a unified format in the sense that it has to be represented as two formulas. This paper proposes a unified weight formula for sample variance calculation from weighted successive differences. A proof is provided to show that sample variance calculated using the proposed unified weighted formula is mathematically equivalent to the basic definition.